Higher Education, Student Health, and Obesity in Developing Countries - Taylor, Caitriona (International Higher Education, 2017)
A dichotomy exists in obesity rates and physical health factors, between similarly situated population groups in developed and developing nations. Positive correlations between higher education levels and obesity in the developed world may not be mirrored in the developing world. Using Egypt as a case study, this paper argues that higher education institutions in developing countries need to be a driving force in creating a cultural of health among their student populations, through increasing access to and participation in physical activity.